Implementasi Aplikasi Google Classroom Dalam Pembelajaran Daring Masa Pandemi Covid-19 Di SMP Swasta Bahalbatu Tahun Ajaran 2021/2022 - Grace Lamudur Arta Sihombing (Institut Agama Kristen Negeri Tarutung, 2022)
Abstract:The aims of this research are :(1) to find out how to implement the application google classroom on online learning mathematics during the Pandemic, and (2) To find out student learning outcomes in implementing the google classroom in online learning mathematics during the Covid-19 pandemic. This research was conducted by SMP Swasta Bahalbatu, the subjects in this study were the headmaster, mathematics teacher, students of class VIII A totaling 32 people. The method used in this research is to use a qualitative approach with a descriptive method. Data collection techniques used are observation, interviews, documentation and tests in the form of essays. Data analysis techniques consist of data reduction, data presentation, and drawing conclusions. The results of the study revealed that: (1) the implementation of the google classroom application in online learning on mathematics subjects during the Covid-19 pandemic, which showed that from all aspects of student learning activities an average score of 1.12 was obtained with the criteria not being implemented and aspects of teacher teaching creativity. obtained an average value of 3.60 with very implemented criteria. (2) the mathematics learning outcomes of students class VIII A implementing the google classroom application in online learning mathematics during the Covid-19 Pandemic at SMP Swasta Bahalbatu from 32 students there were 18 students who completed with an average score of 57.03 and a percentage of completeness 56.25% and included in the poor category.Keywords: google classroom, online learningAbstrak:Penelitian bertujuan untuk : (1) untuk mengetahui bagaimana implementasi aplikasi google classroom pada pembelajaran online pada masa Pandemi covid 19, dan (2) Untuk mengetahui Hasil Belajar siswa dalam mengimplementasikan aplikasi google classroom pada pembelajaran online mata pelajaran matematika pada masa Pandemi Covid-19. Penelitian ini dilaksanakan di SMP Swasta Bahalbatu, subjek dalam penelitian ini adalah Kepala Sekolah, Guru matematika, siswa kelas VIII A yang berjumlah 32 orang. Metode yang dilakukan dalam penelitian ini adalah menggunakan pendekatan kualitatif dengan metode deskriptif. Teknik pengumpulan data yang digunakan adalah observasi, wawancara, dokumentasi dan tes berupa Essay. Teknik analisis data terdiri dari reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian mengungkapkan bahwa: (1) implementasi aplikasi google classroom dalam pembelajaran online pada mata pelajaran matematika masa Pandemi Covid-19 menunjukkan bahwa dari keseluruhan aspek aktivitas belajar siswa diperoleh nilai rata-rata 1,12 dengan kriteria kurang terlaksana dan aspek kreativitas mengajar guru diperoleh nilai rata-rata 3,60 dengan kriteria sangat terlaksana. (2) hasil belajar siswa kelas VIII A pada mengimplementasikan aplikasi google classroom pada pembelajaran online matematika masa Pandemi Covid-19 di SMP Swasta Bahalbatu dari 32 siswa terdapat 18 siswa yang tuntas dengan skor rata-ratanya 57,03 dan persentase ketuntasan 56,25% dan termasuk dalam kategori kurang baik.Kata Kunci: aplikasi google classroom, pembelajaran online